Hypofractionation of partial breast irradiation using radiobiological models. Issue 8 (December 2015) - Avanzo, Michele; Trovo, Marco; Stancanello, Joseph; Jena, Rajesh; Roncadin, Mario; Toffoli, Giulia; Zuiani, Chiara; Capra, Elvira
Highlights: We design hypofractionation for partial breast irradiation using tumor BED and NTCP for moderate/severe RIF. Treatments with 35 Gy/7f and 28 Gy/f were selected for fraction reduction from an initial treatment of 40 Gy/10f. Incidence of moderate/severe RIF in the first hypofractionated treatment was only 5.3%. NTCP for moderate/severe RIF with the correction for incomplete repair was the most accurate. The α/β of 3 Gy used for moderate/severe RIF was consistent with our clinical results. Abstract: Purpose: To reduce the fraction number in Partial Breast Irradiation (PBI) with initial prescription of 40 Gy in 10 fractions using radiobiological models with specific focus on risk of moderate/severe radiation-induced fibrosis (RIF) and report clinical results. Methods and materials: 68 patients (patient group A) were treated with 40 Gy in 10 fractions delivered by field-in-field, forward-planned IMRT. Isotoxic regimens with decreasing number of fractions were calculated using Biological Effective Dose (BED) to the breast. Risk for RIF in hypofractionated treatment was predicted by calculating NTCP from DVHs of group A rescaled to fractions and dose of novel regimens. Moderate/severe RIF was prospectively scored during follow-up. Various NTCP models, with and without incomplete repair correction, were assessed from difference to observed incidence of RIF. In order to verify the value for α/β of 3 Gy assumed for breast, we fitted α/β to observed incidences of moderate/severe RIF. Results: Treatments with 35 Gy/7f and 28 Gy/4f were selected for the fraction reduction protocol. 75 patients (group B) were treated in 35 Gy/7f. Incidence of moderate/severe RIF was 5.9% in group A, 5.3% in group B. The NTCP model with correction for incomplete repair had lowest difference from observed RIF. The α/β obtained from fitting was 2.8 (95%CIs 1.1–10.7) Gy. Conclusions: The hypofractionated regimen was well tolerated. The model for NTCP corrected for incomplete repair was the most accurate and an assumed α/β value of 3 Gy is consistent with our patient data. The hypofractionation protocol is continuing with patients treated with 28 Gy/4f.